Effect of Age at First Calving on Milk Production and Reproductive Performance of Indonesian Holstein Dairy Cattle - Yuliati Wahyu Setyorini; Edy Kurnianto; Sutopo Sutopo; Sutiyono Sutiyono (Buletin Peternakan, 2022)
The purpose of this study was to determine the milk production and reproductive performance of dairy cattle in groups of different ages at first calving and to elucidate the effect of age at first calving on milk production and calving interval of Indonesian Holstein dairy cattle. The observation method use in this study. Records of 80 dairy cows which were born in Indonesia and had the age at first calving range of 23-32 months were used as the materials. Cows were divided into two groups based on age at first calving (AFC). Group I was cows with age at first calving of 23-27 months and group II with age at first calving of 28-32 months. The parameters observed were the total milk yield, calving interval, post-partum mating, interval from calving to conception, and service per conception. To compare data between two groups, the t-tests and descriptive analysis were used. The results showed that the total milk yield, calving interval, postpartum mating, interval from calving to conception, and service per conception in the group I did not have a significant difference from the group II. The linear regression analysis showed that the age at first calving had a weak negative effect on the total milk yield, and the age at first calving had a weak positive effect on the calving interval. In conclusion, the difference in the age at first calving did not provide a different performance on milk production and reproduction of dairy cattle